FLRT2 mediates chondrogenesis of nasal septal cartilage and mandibular condyle cartilage - Xie Tao; Zhu Fangyong; Cheng Renyi; Gao Jing; Hong Yuchen; Deng Peishen; Liu Chaofeng; Xu Yanhua (Open Medicine, 2024)
Nasal septal cartilages (NSCs) and mandibular condyle cartilages (MCCs) are two important cartilages for craniomaxillofacial development. However, the role of FLRT2 in the formation of NSCs and MCCs remains undiscovered. NSCs and MCCs were used for immunocytochemistry staining of collagen II, toluidine blue staining, and alcian blue staining. Quantitative reverse transcription‑PCR and western blot were used to detect mRNA and protein expressions of FLRT2, N-cadherin, collagen II, aggrecan, and SOX9. Cell proliferation of MCCs and NSCs was tested by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and cell counting kit‑8 assay. Cell migration of MCCs and NSCs was examined by wound healing assay and Transwell. Chondrogenesis of MCCs and NSCs were similar in morphological characteristics, while different in cell proliferation, migration, and extracellular matrix. FLRT2 promotes the proliferation and migration of NSCs. There were up-regulation of N-cadherin and down-regulation of collagen II, aggrecan, and SOX9 in NSC with knock down FLRT2. The current study, as demonstrated by Xie et al., reveals that FLRT2 overexpression in Sprague-Dawley neonatal rats promotes the proliferation and migration of NSCs and MCCs, decreases N-cadherin while increases collagen II, aggrecan, and SOX9 in NSC and MCCs. Altogether, FLRT2 mediates chondrogenesis of NSCs and MCCs.